Effect of 3-Nitroacetophenone on Corrosion Inhibition of Mild Steel in Acidic Medium - Sani Ibrahim; R. Sanmugapriya; J. Arockia Selvi; T. Pushpa Malini; P. Kamaraj; P. A. Vivekanand; Govindasami Periyasami; Ali Aldalbahi; Karthikeyan Perumal; J. Madhavan; Santosh Khanal (International Journal of Photoenergy)
Acetophenone derivatives are eco-friendly corrosion inhibitors to prevent corrosion of mild steel (MS) in acidic medium. In this work, the inhibition effect of 3-nitroacetophenone (3-NA) on the corrosion of MS in acidic medium (1 N HCl) was investigated using weight loss measurements, electrochemical measurements, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and quantum chemistry analysis. The studies were performed using different concentrations of inhibitors and at different temperatures. The results indicated that the inhibition efficiency of 3-NA increases with an increase in inhibitor concentration and reaches to a maximum of 64% at inhibitor concentration of 250 ppm at 30°C. The potentiodynamic polarization measurement indicated that 3-NA acts as mixed category of interdict. The adsorption of 3-NA on MS surface followed the Langmuir adsorption isotherm. The mode of adsorption of 3-NA on MS surface was further studied by quantum chemical calculations based on density functional theory (DFT). The results plainly revealed that 3-NA performs fairly as corrosion interdict for MS in acidic medium.